Impact of mcr-1 on the Development of High Level Colistin Resistance in Klebsiella pneumoniae and Escherichia coli - Zhu, Xiao-Qing; Liu, Yi-Yun; Wu, Renjie; Xun, Haoliang; Sun, Jian; Li, Jian; Feng, Yaoyu; Liu, Jian-Hua (Frontiers in Microbiology, 2021)
Plasmid-mediated colistin resistance gene mcr-1 generally confers low-level resistance. The purpose of this study was to investigate the impact of mcr-1 on the development of high-level colistin resistance (HLCR) in Klebsiella pneumoniae and Escherichia coli. In this study, mcr-1-negative K. pneumoniae and E. coli strains and their corresponding mcr-1-positive transformants were used to generate HLCR mutants via multiple passages in the presence of increasing concentrations of colistin. We found that for K. pneumoniae, HLCR mutants with minimum inhibitory concentrations (MICs) of colistin from 64 to 1,024 mg/L were generated. Colistin MICs increased 256- to 4,096-fold for mcr-1-negative K. pneumoniae strains but only 16- to 256-fold for the mcr-1-harboring transformants. For E. coli, colistin MICs increased 4- to 64-folds, but only 2- to 16-fold for their mcr-1-harboring transformants. Notably, mcr-1 improved the survival rates of both E. coli and K. pneumoniae strains when challenged with relatively high concentrations of colistin. In HLCR K. pneumoniae mutants, amino acid alterations predominately occurred in crrB, followed by phoQ, crrA, pmrB, mgrB, and phoP, while in E. coli mutants, genetic alterations were mostly occurred in pmrB and phoQ. Additionally, growth rate analyses showed that the coexistence of mcr-1 and chromosomal mutations imposed a fitness burden on HLCR mutants of K. pneumoniae. In conclusion, HLCR was more likely to occur in K. pneumoniae strains than E. coli strains when exposed to colistin. The mcr-1 gene could improve the survival rates of strains of both bacterial species but could not facilitate the evolution of high-level colistin resistance.